Students' and lecturers' perspectives on the implementation of online learning in medical education due to COVID-19 in Germany: a cross-sectional pilot study - Hertling, Stefan F.; Back, David A.; Kaiser, Mario; Loos, Franziska M.; Schleußner, Ekkehard; Graul, Isabel (Frontiers in Medicine, 2023)
Background: With the advent of the COVID-19 pandemic, the challenge is to transform medical teaching into digital medical teaching in a short period of time. Objective: Therefore, this study investigated an evaluation of an elective module by medical students and teachers in the traditional form in person and during the COVID-19 pandemic in a virtual teaching form. Methods: Using the elective module "Sports Medicine", which includes both lectures and practical units, the opinions of the medical students about conventional teaching compared to digital instruction was evaluated. In the winter semester 2019/2020, all classes were taught face-to-face and had to be switched to virtual teaching in the summer semester 2020 on an ad hoc basis due to the pandemic. Students were asked to answer questions on general conditions, participant behavior, instructor evaluation, skill acquisition, topic selection, and an overall evaluation after both forms of teaching. Likewise, the lecturers of both courses were interviewed in semiqualitative interviews about the same topics. Descriptive data analysis was performed to process the data. Results: The students perceived digital teaching to be superior in most sub-areas, compared to in person teaching, concerning framework, instructor evaluation, skill acquisition, topic selection, and an overall rating. Medical students seemed to feel better with digital teaching in most areas of evaluation. The lecturers found the new form of teaching rather unsettling and criticized the lack of verbal and especially non-verbal communication, as well as the short preparation time for the new challenge. The instructors were uncomfortable with some aspects of the virtual teaching format. Conclusion: In the wake of the Covid-19 pandemic, medical schools should rapidly digitize their teaching offerings and support faculty members in their computer-based competence with continuing education opportunities and time resources.